Endothelial Cell Membrane Sensitivity to Shear Stress is Lipid Domain Dependent - Tabouillot, Tristan (2011)
Blood flow-associated shear stress causes physiological and pathophysiological biochemical processes in endothelial cells that may be initiated by alterations in plasma membrane lipid domains characterized as liquid-ordered (l(o)), such as rafts or caveolae, or liquid-disordered (l(d)). To test for domain–dependent shear sensitivity, we used time-correlated single photon counting instrumentation to assess the photophysics and dynamics of the domain-selective lipid analogues DiI-C(12) and DiI-C(18) in endothelial cells subjected to physiological fluid shear stress. Under static conditions, DiI-C(12) fluorescence lifetime was less than DiI-C(18) lifetime and the diffusion coefficient of DiI-C(12) was greater than the DiI-C(18) diffusion coefficient, confirming that DiI-C(12) probes l(d), a more fluid membrane environment, and DiI-C(18) probes the l(o) phase. Domains probed by DiI-C(12) exhibited an early (10 s) and transient decrease of fluorescence lifetime after the onset of shear while domains probed by DiI-C(18) exhibited a delayed decrease of fluorescence lifetime that was sustained for the 2 min the cells were subjected to flow. The diffusion coefficient of DiI-C(18) increased after shear imposition, while that of DiI-C(12) remained constant. Determination of the number of molecules (N) in the control volume suggested that DiI-C(12)-labeled domains increased in N immediately after step-shear, while N for DiI-C(18)-stained membrane transiently decreased. These results demonstrate that membrane microdomains are differentially sensitive to fluid shear stress.